New food product purchase activities and factors affecting consumer behavior a correlational study - Tagura, Carl Justine Gumapac (College of Home Economics, University of the Philippines Diliman, 2023)
This study aims to investigate the purchase activities of selected state university students towards new food products and identify its relationship towards factors affecting consumer purchasing behavior and also their socio-demographic profile. It is a correlational quantitative research design, with self-administered questionnaires as the means of gathering the data. The total participants of this study are 73 college students, chosen through two stage sampling. Using the four academic clusters in the university, the researcher randomly selected two colleges. The chosen colleges were then subjected to proportional sampling in order to find the total number of respondents for each cluster. Descriptive statistics, Cramer’s V, Spearman’s Rank Correlation, and Multiple Linear Regression were used to summarize and analyze the data. The results showed that food neophilia, health consciousness, food’s perceived safety and packaging, social contacts, and capability to purchase (as determined by family income) are factors that are correlated with college students’ propensity to purchase new food products. In particular, food neophilia, perceived safety, and perceived packaging can significantly predict college students’ likelihood of purchasing new food products. Given these findings, it is recommended for entrepreneurs to enhance the packaging aspects of their products and also prioritize the safety aspects of their products. They can also capitalize on the food neophilia tendencies of their customers by enhancing the awareness and information of their new food products. To improve the validity of the research and extend its generalizability, refinement of the instrument that measures the significant predictors is recommended. It is also recommended that new factors or variables that can explain new food product purchase may be explored given the low but significant predicting ability of the model used in this study.